DOES HINDI CINEMA SPEAK FOR VAISHYA SUBALTERN WOMEN? - Avantika; Thakran, Annu; Sharma, Dipika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Nation building is a historical creation and it has not been created outside its premises. By examining history, it is seen that the nation is formed in the interest of certain castes and certain linguistic-regional-cultural communities. It remains a multi-faceted campaign to fulfill the demands of these particular castes. If nations are symbols of progress and freedom, then for many they can also become sources of oppression. Scholars associated with the subaltern studies had declared that they would try to turn history in this direction by writing history from the point of view of the people, Ranjit Guha was the first to take the initiative in this. Cinema is an emerging form of literature, it is a medium to bring stories into existence by adopting the society itself. With time and history, Hindi cinema has presented the subaltern class and group in front of the audience. Those who were not given a place in the society and were not accepted. One such class is: - Vaishya women, who were never given any status in the society except as sex objects! Through this research paper, we will study and analyze whether Hindi cinema has become the ’heart voice’ of Vaishya subaltern women and has been able to convey their words, exploitation, and struggle to the audience. How does Hindi cinema present their voice through its dialogues and conversations? For this study, Hindi films Begum Jaan (2017) and Gangubai Kathiawadi (2022) and other films made in contemporary times have been included as per the study objective. It is clear that Hindi cinema, along with being a medium of expression, is helpful in presenting the everyday struggle on the platform and speaks for the rights of Vaishya women by becoming their heart voice.